Clinical Trial of the Potassium Channel Activator Diazoxide for Major Depressive Disorder Halted Due to Intolerability. Issue 3 (June 2018) - Kadriu, Bashkim; Yuan, Shiwen; Farmer, Cristan; Nugent, Allison C.; Lener, Marc S.; Niciu, Mark J.; Park, Minkyung; Yazdian, Aaron; Ballard, Elizabeth D.; Henn, Fritz A.; Henter, Ioline D.; Park, Lawrence T.; et al.
Abstract: Background: Some glutamatergic modulators have demonstrated rapid and relatively sustained antidepressant properties in patients with major depressive disorder. Because the potassium channel activator diazoxide increases glutamate uptake via potassium channel activation, we hypothesized that it might exert antidepressant effects by increasing the removal of glutamate from the synaptic cleft, thereby reducing excessive glutamate transmission. Methods: This randomized, double-blind, placebo-controlled, crossover, single-site inpatient clinical study was conducted at the National Institute of Mental Health to assess the efficacy and safety of a 3-week course of diazoxide (200–400 mg daily, twice a day) versus a 3-week course of placebo in 6 participants with treatment-refractory major depressive disorder. The primary clinical outcome measure was change in Montgomery-Asberg Depression Rating Scale score from baseline to posttreatment. Quantitative insulin sensitivity check index, as well as concomitant imaging measures (electroencephalography, proton magnetic resonance spectroscopy, magnetoencephalography), were used as potential surrogate markers of target (KATP channel) engagement. Results: The study was halted due to severe adverse effects. Given the small sample size, statistical evaluation of the effect of diazoxide on Montgomery-Asberg Depression Rating Scale scores or the imaging measures was not pursued. Visual inspection of the quantitative insulin sensitivity check index test revealed no evidence of target engagement. Conclusions: Although the results are negative, they are an important addition to the literature in this rapidly changing field.